Perceived Obstacles to Diabetes Care and Self-Management and Their Sociodemographic Correlates Among Adults in Central Java, Indonesia - Kusumaningrum, Niken Safitri Dyan; Handayani, Fitria; Cahyani, Zulfida Rahma; Nilamsari, Nur Suci; Utami, Estuning Budi; Puspitasari, Monica Adelia; Lusiana, Khofifah (Nurse Media Journal of Nursing, 2026)
Background: Effective diabetes management requires sustained commitment and heightened awareness. Individuals with diabetes often face multiple obstacles that affect daily functioning and long-term health outcomes. However, evidence describing specific obstacles among people with diabetes in Indonesia, particularly in Central Java, remains limited.Purpose: This study aimed to examine the prevalence and domains of perceived diabetes-related obstacles among adults living with diabetes and to assess their associations with sociodemographic characteristics.Methods: A cross-sectional study was conducted among individuals with diabetes attending public health centres in Semarang, Central Java, Indonesia. Participants were consecutively recruited if they were aged ≥18 years, had a confirmed diagnosis of diabetes, and had no known cognitive impairment. Individuals who were acutely ill were excluded. Data were collected using the 57-item Bahasa Indonesia version of the Diabetic Obstacle Questionnaire (DOQ), which covers eight domains of diabetes-related challenges. Independent t-tests and multiple linear regression were used to examine associations between obstacle scores and selected sociodemographic characteristics.Results: A total of 237 participants were included (mean age = 61.96 years), the majority of whom were female, with a mean diabetes duration of 8.16 ± 7.39 years. The highest perceived obstacles were observed in the diagnosis domain (−21.36 ± 33.39). Bivariate analysis showed that education level (p = .002) and diabetes duration (p = .045) were significantly associated with obstacles related to knowledge and beliefs, while random blood glucose level was associated with obstacles related to advice and support (p = .029). Multivariable analysis further identified education level, employment status, diabetes duration, and glycaemic control as significant predictors across selected domains.Conclusion: Although perceived barriers to diabetes management were generally low, challenges persist in the domains of diagnosis, knowledge, and support. These findings highlight the influence of sociodemographic and clinical factors, as well as sociocultural context, in shaping diabetes-related obstacles. Culturally responsive, person-centred interventions are needed to improve self-management and health outcomes.